Cultivos asociados en la Agricultura Sustentable en el Ecuador - Andrade Monar, Edwin Humberto (2022)
This document refers to associated crops in Sustainable Agriculture in Ecuador. Obtaining better production is an essential aspect in the development of sustainable agriculture. The different crops refer to the importance of increasing their production through the use of adequate technology, with an integrated management of cultivars through environmentally friendly products, which contribute to improving soil conditions, environment and improve health conditions. of human beings when consuming organic products. The conclusions determine that it is necessary to associate crops, in order to take advantage of various processes such as soil, climate, cultivar management and mechanisms that allow the use of all available resources (fertilizers, pesticides, water) jointly, saving production costs and applying products that do not pollute the environment; In Ecuador, it has become important and there is currently a favorable attitude on the part of farmers to use bio-inputs and reduce the application of agrochemicals, since the results obtained have generated confidence and credibility in farmers about the use of microorganisms in agriculture as a integrated crop management component that allows protecting the environment and offering clean products benefiting the health of the consumer and the association of crops allows satisfying human needs for fiber and food; improve environmental quality and the natural resource base on which the agricultural economy depends; make efficient use of non-renewable resources; sustain the economic viability of agricultural activities and increase the quality of life of farmers.